Magnesium Ions Moderate Calcium-Induced Calcium Release in Cardiac Calcium Release Sites by Binding to Ryanodine Receptor Activation and Inhibition Sites - Iaparov, Bogdan; Baglaeva, Iuliia; Zahradník, Ivan; Zahradníková, Alexandra (Frontiers in Physiology, 2022)
Ryanodine receptor channels at calcium release sites of cardiac myocytes operate on the principle of calcium-induced calcium release. In vitro experiments revealed competition of Ca2+ and Mg2+ in the activation of RyRs as well as inhibition of RyRs by Mg2+. The impact of RyR modulation by Mg2+ on calcium release is not well understood due to the technical limitations of in situ experiments. We turned instead to an in silico model of a calcium release site (CRS), based on a homotetrameric model of RyR gating with kinetic parameters determined from in vitro measurements. We inspected changes in the activity of the CRS model in response to a random opening of one of 20 realistically distributed RyRs, arising from Ca2+/Mg2+ interactions at RyR channels. Calcium release events (CREs) were simulated at a range of Mg2+-binding parameters at near-physiological Mg2+ and ATP concentrations. Facilitation of Mg2+ binding to the RyR activation site inhibited the formation of sparks and slowed down their activation. Impeding Mg-binding to the RyR activation site enhanced spark formation and speeded up their activation. Varying Mg2+ binding to the RyR inhibition site also dramatically affected calcium release events. Facilitation of Mg2+ binding to the RyR inhibition site reduced the amplitude, relative occurrence, and the time-to-end of sparks, and vice versa. The characteristics of CREs correlated dose-dependently with the effective coupling strength between RyRs, defined as a function of RyR vicinity, single-channel calcium current, and Mg-binding parameters of the RyR channels. These findings postulate the role of Mg2+ in calcium release as a negative modulator of the coupling strength among RyRs in a CRS, translating to damping of the positive feedback of the calcium-induced calcium-release mechanism.